Réponses

2012-05-12T16:18:44+02:00

a) 3x-5 = 2x+9

    3x-2x-5=2x-2x+9

    x-5 = 9

    x-5+5 = 9+5

    x = 14

 

b) 17x-11 = 18x+14

    17x-18x-11 = 18-18 + 14

     -1x - 11 +11 = 14 + 11

      -1x = 25

      x = -25

 

c) 48x-37 = 13x+13

    48x -13x - 37 = 13x-13x + 13

    35x - 37 = 13

    35x - 37 + 37 = 13 + 37

    35x = 50

    ---     ---

    35      35

 

x = 50/35

 

d) 7x-13 = 5x+33x

    7x-5x-13 = 5x-5x + 33x

    2x - 13 = 33x

    2x = 33x + 13

    2x - 33x = 33x - 33x + 13

    -31x = 13

    -----    ----

     -31     -31

 

x = 13/-31